2009
DOI: 10.1016/j.coldregions.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Column Test: Test effectiveness, spatial variability, and comparison with the Propagation Saw Test

Abstract: The Extended Column Test (ECT) is a new stability test that aims to assess the fracture propagation potential across a 90 cm wide isolated column. Initial results with a dataset consisting of over 300 tests collected by one observer demonstrated the ECT's effectiveness for differentiating between stable and unstable slopes. Further, we have received positive feedback on the test from a world-wide network of observers. This paper: 1) presents new recording standards for the test, 2) uses the SnowPilot dataset t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 11 publications
4
58
1
Order By: Relevance
“…For specifics on the particle tracking methodology, see previous work on particle tracking with stability tests (van Herwijnen and Jamieson, 2005;van Herwijnen and Heierli, 2009;van Herwijnen et al, 2010;Bair et al, 2012;. Similar to another study , we found it was often not possible to track particles near the shovel during ECTs because of snow compaction under the shovel.…”
Section: Particle Trackingsupporting
confidence: 72%
See 4 more Smart Citations
“…For specifics on the particle tracking methodology, see previous work on particle tracking with stability tests (van Herwijnen and Jamieson, 2005;van Herwijnen and Heierli, 2009;van Herwijnen et al, 2010;Bair et al, 2012;. Similar to another study , we found it was often not possible to track particles near the shovel during ECTs because of snow compaction under the shovel.…”
Section: Particle Trackingsupporting
confidence: 72%
“…The selected tests had similar collapse amplitudes a (3-9 mm) to those in other studies of failures on persistent weak layers (van Herwijnen and Jamieson, 2005;van Herwijnen et al, 2010;. Plotting horizontal position against collapse amplitude shows that a steady state was not reached, even after almost 7 m (Fig.…”
Section: Collapse Amplitudementioning
confidence: 75%
See 3 more Smart Citations